Asia-Pacific judiciaries : independence, impartiality and integrity / edited by Hoong Phun (H.P.) Lee, Monash University, Marilyn Pittard, Monash University. - Lee, H. P., 1947-; Pittard, Marilyn J. (Cambridge University Press, 2018)
Judicial independence, integrity and impartiality are crucial to public trust in the judiciary. Justice must also be seen to be dispensed fairly and without fear or favour. In the context of themes and perspectives as well as comparative theories of independence, this book provides a contemporary analysis of the role and independence of judges in 15 countries in the Asia-Pacific. Expert analyses include countries that are governed by authoritarian governments or are beset by dramatic government changes, which undermine judges by attacking and preventing their independence, to more democratic countries where there are strides towards judicial independence. The problems confronting judges and courts are explained and analysed, with the aim of establishing a commonality of standards which can be developed to strengthen and promote the important values of judicial independence, impartiality and integrity. Solutions for the Asia-Pacific region are also proposed.